The Benefits of Grammarly for Reducing Errors in Student's Academic Writing - Cahya Aprilya, Rara; Pritaputri Ramadhan , Dinda; Hazana, Melisa; Pauziansah, Eki; Pohan, Erwin (Universitas PGRI Adi Buana Surabaya, 2025)
This study explores the benefits of Grammarly as a tool for reducing errors in students' academic writing. Writing is one of the most challenging language skills due to the complexity of grammar, vocabulary, and idea organization. This study examines the benefits of Grammarly in improving students’ writing quality through an analysis of empirical studies published between 2018–2023. The review results show that Grammarly provides real-time feedback that helps students correct grammar and spelling errors, and improves the clarity and coherence of their academic writing. In addition, Grammarly helps maintain consistency in tone and style of writing and enriches vocabulary, which contributes to improving the quality of writing. Case studies show its effectiveness in identifying mechanical errors, enhancing vocabulary, and providing feedback that complements manual correction methods. In conclusion, Grammarly greatly helps students improve the quality of their writing by reducing errors and improving the clarity and coherence of their writing.